2017
DOI: 10.1007/978-3-319-61276-8_102
|View full text |Cite
|
Sign up to set email alerts
|

Control of Force Impulse in Human-Machine Impact

Abstract: The clinical study of postural control requires a disturbance to be imposed to the subject under evaluation. Among various kinds of disturbance, a mechanical stimulation, consisting in an impulsive force impressed to a certain point of the body, can be used. This paper describes the study of a device conceived to generate such a disturbance. The device is based on a commercial pneumatic actuator, equipped with appropriate force and motion feedback sensors, and properly controlled. The major item is to take int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Using a second admittance controller, this force was used to extend or lower the robot's end-effector. The authors that employed this controller approached the mobile robot helper's base to perform the cooperative carrying of a load [52,53]. The authors of [54,55] also used a lifting controller with cascaded second-order virtual admittance controllers applied to the same applications.…”
Section: Impedance Control Strategymentioning
confidence: 99%
“…Using a second admittance controller, this force was used to extend or lower the robot's end-effector. The authors that employed this controller approached the mobile robot helper's base to perform the cooperative carrying of a load [52,53]. The authors of [54,55] also used a lifting controller with cascaded second-order virtual admittance controllers applied to the same applications.…”
Section: Impedance Control Strategymentioning
confidence: 99%
“…The proposed method was implemented and tested using a robotic manipulator and a force sensor. The results showed that the proposed strategy effectively regulated the force impulse during impact, leading to improved safety during human-robot interactions [22].…”
Section: Contact Detection and Mitigationmentioning
confidence: 99%